Prediction-based prompt levothyroxine replacement to prevent a hypothyroid state after immune-related adverse events involving the thyroid gland - Ichiro Yamauchi; Takuro Hakata; Taku Sugawa; Daisuke Kosugi; Haruka Fujita; Kentaro Okamoto; Yohei Ueda; Toshihito Fujii; Daisuke Taura; Norio Harada; Nobuya Inagaki (Endocrine Journal)
Immune checkpoint inhibitors (ICIs) are used for various malignancies, although they frequently cause immune-related adverse events involving the thyroid gland (thyroid irAEs). We conducted a retrospective cohort study to elucidate thyroid function outcomes. Fifty of 639 patients who received PD-1 blockade therapy met criteria and were divided into the following groups: thyrotoxicosis with subsequent hypothyroidism (Toxic-Hypo, n = 21); thyrotoxicosis without subsequent hypothyroidism (Toxic, n = 9); and hypothyroidism without prior thyrotoxicosis (Hypo, n = 20). The Toxic-Hypo group developed thyroid irAEs earlier than the Toxic group (26 vs. 91 days; p < 0.001), and had higher serum free T4 levels (3.210 vs. 1.880 ng/dL; p = 0.011). In addition, positive anti-thyroglobulin antibodies (TgAbs) at thyroid irAE onset were more common in the Toxic-Hypo group (93.3%) than in the Toxic group (0.0%; p = 0.005) and Hypo group (44.4%; p = 0.007). The Toxic-Hypo group developed severe hypothyroidism and required larger levothyroxine (LT4) doses than the Hypo group (75 vs. 25 μg/day; p = 0.007). We predicted that patients with positive TgAbs who developed severe thyrotoxicosis within 4 weeks after the first ICI administration would develop subsequent hypothyroidism. We treated 4 such patients with prompt LT4 replacement, characterized by LT4 initiation after thyrotoxicosis improvement and quick dose titration. Their euthyroid state was successfully maintained, in contrast with patients receiving conventional replacement. In conclusion, rapid-onset severe thyrotoxicosis in patients with TgAbs correlated with a high likelihood of subsequent hypothyroidism. Accordingly, prompt LT4 replacement is suggested to prevent a severely hypothyroid state.